Interweaving letters and sounds : the impact of phonics instruction in English on the oral production and symbolic representation of sounds among university-level L2 English learners - Capell, Martín (2018)
The study described in this thesis was conducted with a number of L1 Spanish learners of L2 English who were students of English Pronunciation Practice (EPP), an undergraduate pronunciation course taught in English Teaching, Translation and Research programs at Facultad de Lenguas (FL), Universidad Nacional de Córdoba (UNC). It was aimed at investigating whether explicit phonics instruction contributes positively to the oral production and phonemic transcription of unfamiliar words of a number of university-level L1 Spanish learners of L2 English. A quasi-experimental research designed was used and the data obtained were analyzed with a quantitative method. The participating students were divided into experimental and control groups. The total number of students whose performance was analyzed was 62 (experimental = 33 and control = 29). Both groups were pretested on oral production and phonemic transcription of unfamiliar words. Next, the experimental group received a six-lesson phonics instruction focusing on the pronunciation and transcription of six specific orthographic combinations. After that both groups were posttested in terms similar to the pretest. All the data collected were analyzed using the dependent t test (also known as paired t test) to assess the difference between the averages obtained in the pretest and posttest conditions by each group. This was complemented with a variability analysis conducted to determine the degree of difficulty caused by the different combinations to the participating students. The results obtained from this study confirm the hypothesis that students who received explicit phonics instruction performed better in terms of oral production and phonemic transcription of unfamiliar words containing the orthographic combinations chosen than did students who did not receive such instruction. Pedagogical implications, practical applications and directions for future research are given.